(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
The article analyzes the phonetic features of Belarusian origin that form a specific current dialects of northern part of Novgorod-Seversky district in Chernihisk region and their influence on the determination of their place in the system of the Eastern Polissian dialect of the Ukrainian language.